2018
DOI: 10.1007/s11250-018-1524-8
|View full text |Cite
|
Sign up to set email alerts
|

Haematological, biochemical and organ changes in broiler chickens fed varying levels of Morinda lucida (brimstone) leaf meal supplementation in the diets

Abstract: The aim of this study was to evaluate the effects of dietary supplementation of Morinda lucida leaf meal (MLLM) on the haematology, biochemical and organ changes of broiler chickens. One hundred and ninety-eight day-old Marshall broiler chicks were completely randomised into 6 treatments in a 3 × 2 factorial arrangement of three levels of M. lucida leaf meal supplementation (0, 0.1 and 0.2 g/kg) with or without medication. The treatment consisted of both negative (without MLLM and routine medication) and posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Better feed conversion ratio obtained for guinea fowls fed the diet with HB could be attributed to the additive effect of antimicrobial properties exhibited by constituent scent leaf (Prabhu et al, 2009), antioxidant and antimicrobial properties of turmeric (Quiles et al, 2002), and moringa leaf (Ogundare & Onifade, 2009) contained in the blend. Previous studies also reported improved growth of broilers following dietary inclusion of Morinda lucida leaf meal (Lala et al, 2017) and turmeric powder (Ahmadi, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Better feed conversion ratio obtained for guinea fowls fed the diet with HB could be attributed to the additive effect of antimicrobial properties exhibited by constituent scent leaf (Prabhu et al, 2009), antioxidant and antimicrobial properties of turmeric (Quiles et al, 2002), and moringa leaf (Ogundare & Onifade, 2009) contained in the blend. Previous studies also reported improved growth of broilers following dietary inclusion of Morinda lucida leaf meal (Lala et al, 2017) and turmeric powder (Ahmadi, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Humínové látky majú antibakteriálny, antivirotický a antimikrobiálny účinok v chove zvierat, čím zlepšujú ekonomiku a ekológiu v živočíšnej výrobe, najmä zvyšovaním rastu, znižovaním nákladov na kilogram prírastku a minimalizovaním rizika ochorení. Navyše nie sú toxické, ani teratogénne (Lala et al, 2017).…”
Section: Výsledky a Diskusiaunclassified